Life cycle assessment for the production of refined palm products and palm-based biofuels / Yung Chee Liang - Yung , Chee Liang (2021)
Palm oil is an important commodity for Malaysia which contributes 5-7% to the national gross domestic product. Being the second-largest producer in the world, crude palm oil (CPO) production in Malaysia has reached 19.858 million tonnes in 2019. Majority of the CPO produced are refined and fractionated in the local refineries before export or further downstream applications. The main objective of the study is to determine the environmental impacts of palm oil refining, fractionation and biofuels production in Malaysia. For palm oil refining and fractionation, the inventory data are derived from primary data supplied by six palm oil refineries for a period of five years operation. For biodiesel production, the inventory data are derived from primary data collected from six commercial biodiesel plants for a period of three years operation. The inventory data for hydroprocessing are referred to pilot plant operation data due to no commercial hydroprocessing activity in the country. Life cycle assessment (LCA) is conducted using SimaPro software version 9.1.1.1 and impact assessment is performed according to ReCiPe 2016 (Hierarchist) methodology. In the gate-to-gate LCA, bleaching earth, electricity and transportation of CPO are the main contributors to environmental impacts in the palm oil refining stage while RBD palm oil is the single major contributor to the palm oil fractionation stage. Improvement in the transportation of CPO can reduce the environmental impacts effectively in the refinery subsystem through sourcing of CPO from nearby palm oil mills and the use of modern Euro 5-compliant trucks. Methanol, acids and sodium methoxide (transesterification catalyst) are the three major contributors to the environmental impacts in the biodiesel subsystem. Hydrogen and electricity are the two important contributors to the hydroprocessing subsystem. Allocation based on economic value is suitable for LCA of palm oil refining, fractionation and biodiesel production due to different economic values of the products and co-products. Energy allocation based on lower heating values is suitable for the hydroprocessing subsystem since the products and co-products are energy-based. Sensitivity analysis on allocation procedures at refining and fractionation shows an insignificant difference between allocation based on mass and energy content simply due to the similar energy content of the refined and fractionated palm products. Sensitivity analysis on prices movement shows a negligible variation on the allocated environmental impacts for both the refinery and the biodiesel subsystems. The impact assessment of the palm biodiesel subsystem shows that the replacement of fossil-based methanol with biomethanol derived from biogas is the preferred mitigation option. 19% reduction in global warming impact and 60% saving of fossil resources are anticipated for the gate-to-gate impact assessment. The cradle-to-gate and cradle-to-grave LCA highlight the important contribution of biogas emissions from the palm oil mills subsystem to the overall global warming impact. Biogas capturing at palm oil mills and the replacement of fossil-based methanol are the two important strategies to reduce the potential environmental impacts.